2008
DOI: 10.1534/genetics.108.089896
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the Currently Fittest: Genetics of Rainbow Trout Survival Across Time and Space

Abstract: As a fitness trait, survival is assumed to exhibit low heritability due to strong selection eroding genetic variation and/or spatio-temporal variation in mortality agents reducing genetic and increasing residual variation. The latter phenomenon in particular may contribute to low heritability in multigeneration data, even if certain cohorts exhibit significant genetic variation. Analysis of survival data from 10 year classes of rainbow trout reared at three test stations showed that treating survival as a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 64 publications
3
70
0
1
Order By: Relevance
“…Resistances to different mortality factors do not necessarily share a common genetic determination (Gjøen et al, 1997;Henryon et al, 2005;Bubliy & Loeschcke, 2005;Ødega˚rd et al, 2007 ;Kjøglum et al, 2008). This is for example highlighted by the fact that moderate genotyperenvironment interaction was also found for rainbow trout survival during the grow-out period, as shown by the non-unity genetic correlations between environments (Vehvila¨inen et al, 2008 ;present study). Similarly, different alleles of a single gene may provide resistance against different diseases or mortality factors (Shook & Johnson, 1999 ;Grimholt et al, 2003).…”
Section: (Iii) Factors Causing Weak Correlations Between Life Stagesmentioning
confidence: 73%
See 4 more Smart Citations
“…Resistances to different mortality factors do not necessarily share a common genetic determination (Gjøen et al, 1997;Henryon et al, 2005;Bubliy & Loeschcke, 2005;Ødega˚rd et al, 2007 ;Kjøglum et al, 2008). This is for example highlighted by the fact that moderate genotyperenvironment interaction was also found for rainbow trout survival during the grow-out period, as shown by the non-unity genetic correlations between environments (Vehvila¨inen et al, 2008 ;present study). Similarly, different alleles of a single gene may provide resistance against different diseases or mortality factors (Shook & Johnson, 1999 ;Grimholt et al, 2003).…”
Section: (Iii) Factors Causing Weak Correlations Between Life Stagesmentioning
confidence: 73%
“…89) genetically correlated than in the whole data. This sort of difference between datasets is expected if there is spatio-temporal variability in mortality factors causing variation in genetic parameters (Vehvila¨inen et al, 2008). For instance, in our previous study, we showed that heritability for rainbow trout survival during grow-out stage ranges between 0 .…”
Section: (I) Survival Within Fingerling Stagementioning
confidence: 90%
See 3 more Smart Citations